The vitamin and selenium contents of apricot fruit of different varieties cultivated in different geographical regions - Munzuroglu, O; Karatas, F; Geckil, H (Elsevier Sci Ltd, 2003)
High-pressure liquid chromatographic and fluorometric methods were utilized to determine the vitamin (A, C, E and beta-carotene) and selenium levels in apricot fruit. The vitamins (A, C, and E), beta-carotene and selenium levels of both fresh and sulphurized (sulphur-dried) apricot fruit from several common cultivars and wild type, grown in different regions, were analysed. The effects of post-harvest processing, regional difference and cultivar type on the levels of these nutrients were investigated. Cultivated varieties possessed significantly higher vitamin C (P < 0.01), vitamin A and E (P < 0.05) than the wild type. The vitamin C levels of fresh and sulphur-dried apricot from cultivated forms, for example, were 1.8-2.7- and 2.9-4.6-fold, respectively, higher than those of wild type ones. Among cultivated varieties, H cultivar was determined to have significantly highest vitamin A, E and beta-carotene contents (P<0.05). In general, the vitamin, beta-carotene and selenium levels were determined to be significantly different, both between varieties and between different regions within the same variety. Cultivars in region ES, a high altitude region, for example, had significantly (P < 0.05) higher vitamin C content than the same cultivars grown in other regions. The selenium content, however, was significantly (P<0.01) higher only in fresh fruit from variety HB in region ES than the other two regions. (C) 2003 Elsevier Ltd. All rights reserved.
Keywords: apricot; beta-carotene; HPLC; Prunus armeniaca; selenium; vitamins